Malignant ascites-derived exosomes promote peritoneal tumor cell dissemination and reveal a distinct miRNA signature in advanced gastric cancer. (10th August 2019) - Hu, Yanting; Qi, Changsong; Liu, Xiang; Zhang, Cheng; Gao, Jing; Wu, Yi; Yang, Jing; Zhao, Qian; Li, Jian; Wang, Xiaojuan; Shen, Lin
Abstract: Peritoneal dissemination (PD) is the most frequent metastasis with poor prognosis in patients with advanced gastric cancer (GC). However, the molecular mechanisms of PD remain poorly defined. Exosomes play a pivotal role in cancer progression. Thus, this study aims to investigate the effects of malignant ascites (MA)-derived exosomes from GC patients on tumor cells and to elucidate the underlying mechanism. In vitro and in vivo analysis showed that compared to exosome-depleted supernatants, exosomes from MA of GC patients promoted invasion of AGS cells by up-regulation of Epithelial-mesenchymal transition (EMT) signaling. In a mouse abdominal xenograft model, the median survival was shorter after MA-derived exosomes treatment than the control group (35.5 days versus 67 days, p = 0.0005). Moreover, 29 exosomal miRNAs from ascites were identified by high throughput sequencing among 8 paired GC patients before and after peritoneal chemotherapy and 3 individuals with non-malignant disease. In summary, MA-derived exosomes from patients with GC promote EMT signaling in GC cells and in mouse peritoneal tumor model. Differential exosomal miRNAs might be targeted therapeutically for inhibiting peritoneal metastasis, which provides new insights for the molecular mechanisms of PD in GC. Highlights: The molecular mechanism of peritoneal dissemination in advanced gastric cancer is not well defined. We are the first to demonstrate the inducing effect of malignant ascites-derived exosomes on cell invasion via EMT signaling pathway both in vitro and in vivo . Secondly, we found that the specific miRNA profiling between the patients with peritoneal chemotherapy and without peritoneal chemotherapy. Third, we identified top 29 miRNAs among the control subjects and 8 paired gastric cancer patients before and after peritoneal chemotherapy and found some new miRNA candidates associated with the regulation of EMT signaling pathway, which might be a potential therapeutic target for the treatment of gastric cancer patients with peritoneal metastasis in the future.